Styrene-free unsaturated polyester resin and preparation method thereof
By adding cellulose nanocrystals in batches and using the loaded ions of sea squirts and rice husk cellulose nanocrystals, a stable core-shell structure is formed, which solves the problem of unstable molecular weight distribution of hyperbranched resins and improves the mechanical properties and biological phase of the resin. Capacity extends service life.
Patent Information
- Application Number
- CN202411618031.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The molecular weight distribution of existing hyperbranched resins is wide, resulting in unstable properties and it is difficult to achieve stable preparation of hyperbranched resins.
By adding cellulose nanocrystals in batches, the reaction rate and kinetic process are controlled, the reaction path and the stability of the intermediate is adjusted, and the different shapes and load ions of the sea squirt and rice husk cellulose nanocrystals are combined to form a stable core-shell structure and Complex interface, optimize the molecular weight distribution and mechanical properties of hyperbranched polyester.
It realizes hyperbranched polyester with narrower molecular weight distribution and more uniform structure, improves the mechanical properties, heat resistance and biocompatibility of the resin, extends the service life, and improves the overall performance and stability of the resin.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resins, and in particular to a styrene-free unsaturated polyester resin and a preparation method thereof. Background Art
[0002] Unsaturated resin products are widely used in national economic fields such as wind power energy, rail transit, lightweight engineering, environmental protection engineering, energy-saving buildings, home decoration and finishing, which greatly facilitates people's daily life. However, unsaturated resin contains 30-50% styrene as an active diluent, and styrene has a low flash point and is volatile. The most critical thing is that styrene has strong irritation and anesthetic effects, as well as potential carcinogenicity and teratogenicity. Although low styrene volatile resins (resins with low styrene content, resins containing styrene volatility inhibitors) have developed, they cannot fundamentally solve the problem of styrene emissions.
[0003] Chinese patent, application number CN202111633256.2, a method for preparing a flame-retardant styrene-free hyperbranched unsaturated resin, comprising the following steps: heating cellulose nanocrystals, tris (2-hydroxyethyl) isocyanurate and dimethylol propionic acid to melt and react to generate a hydroxyl-containing hyperbranched polyester; adding unsaturated and / or saturated acid anhydride to the hydroxyl-containing hyperbranched polyester for ring-opening addition reaction to generate a carboxyl-containing hyperbranched polyester; adding monohydric alcohol to the carboxyl-containing hyperbranched polyester for end-capping to obtain a hyperbranched unsaturated polyester; using acrylate monomers to dilute the hyperbranched unsaturated polyester to obtain a styrene-free hyperbranched unsaturated resin. The styrene-free hyperbranched unsaturated resin prepared by this invention has the characteristics of high solid and low viscosity, and extremely low VOC emissions, and the cured product has the advantages of good air drying, small shrinkage, good transparency, excellent weather resistance, excellent mechanical properties, etc., and the oxygen index reaches 26%, which can be widely used in rail transportation, building materials and home decoration, automotive interiors, coatings and other fields.
[0004] However, the molecular weight distribution of hyperbranched resins is relatively wide, resulting in unstable properties. Summary of the invention
[0005] The embodiments of the present application provide a styrene-free unsaturated polyester resin and a preparation method thereof, thereby solving the problem in the prior art that the hyperbranched resin has a wide molecular weight distribution, resulting in unstable properties, and achieving a relatively stable hyperbranched resin preparation technology.
[0006] The present application embodiment provides a method for preparing a styrene-free unsaturated polyester resin, specifically: S1, cellulose nanocrystals, tris(2-hydroxyethyl)isocyanurate and dimethylolpropionic acid are mixed with nitrogen, and the temperature is slowly raised to 120°C and then stirred. The reaction temperature is 120-140°C, and the cellulose nanocrystals are added for the second time when the acid value of the reaction system is 100 mgKOH / g, and the stirring is continued until the acid value of the reaction system is ≤2 mgKOH / g to obtain a hydroxyl-containing hyperbranched polyester; the mass ratio of cellulose nanocrystals, tris(2-hydroxyethyl)isocyanurate and dimethylolpropionic acid is 1:3:6; S2, lowering the temperature of the hydroxyl-containing hyperbranched polyester reaction system to 50° C., adding maleic anhydride, slowly heating to 120° C., reacting until the acid value is 260 mgKOH / g, to obtain a carboxyl-containing hyperbranched polyester; wherein the mass ratio of the hydroxyl-containing hyperbranched polyester to the maleic anhydride is 4:5; S3, lowering the temperature of the carboxyl-containing hyperbranched polyester reaction system to 50° C., adding ethylene glycol monoallyl ether, passing nitrogen, slowly heating to 180° C., reacting until the acid value is 18 mgKOH / g, terminating the reaction, and obtaining a hyperbranched unsaturated polyester; the mass ratio of the carboxyl-containing hyperbranched polyester to ethylene glycol monoallyl ether is 5:2; S4. Diluting the hyperbranched unsaturated polyester with hydroxyethyl methacrylate to obtain a styrene-free hyperbranched unsaturated resin; the mass ratio of hydroxyethyl methacrylate to the hyperbranched unsaturated polyester is 3:5.
[0007] Furthermore, the cellulose nanocrystals added for the first time account for 30%-60% of the total amount; the added cellulose nanocrystals are extracted and prepared from ascidian.
[0008] Furthermore, the cellulose nanocrystals added for the second time are extracted and prepared from ascidian.
[0009] Furthermore, the cellulose nanocrystals added for the second time are extracted and prepared from rice husks.
[0010] Furthermore, the cellulose nanocrystals are ion-modified before use.
[0011] Furthermore, the rice husk cellulose nanocrystals are loaded with cations, specifically, the rice husk cellulose nanocrystals and DTAB are respectively dissolved in water and then mixed evenly, stirred overnight, and then centrifuged and filtered to dry.
[0012] Furthermore, the ascidian cellulose nanocrystals are loaded with anions.
[0013] Furthermore, the concentration of the DTAB aqueous solution is 1-20 mol / L.
[0014] Furthermore, the rice husk cellulose nanocrystals are partially subjected to microwave treatment before modification, specifically: 500 watts of power treatment for 10 minutes, wherein the microwave-treated rice husk cellulose nanocrystals account for 20-80% of the total mass.
[0015] A styrene-free unsaturated polyester resin is prepared by the above-mentioned preparation method of the styrene-free unsaturated polyester resin.
[0016] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: First, by adding cellulose nanocrystals in batches, the rate in the initial stage of the reaction is slowed down, making the reaction more stable and controllable, reducing side reactions and uneven product distribution caused by too fast a reaction rate, and keeping the raw material concentration in the reaction system within a relatively stable range, which is conducive to the smooth progress of the reaction and allows the reaction to gradually deepen, thereby obtaining a hyperbranched polyester with a narrower molecular weight distribution and a more uniform structure, and improving key indicators such as the mechanical properties and heat resistance of the resin; adding raw materials in batches changes the kinetics of the reaction, adjusts the reaction path and the stability of the intermediates, and adding some cellulose nanocrystals at the initial stage of the reaction promotes the initial formation of a hyperbranched structure; as the reaction proceeds, gradually adding the remaining raw materials can further improve and optimize the hyperbranched structure.
[0017] Secondly, due to their longer length, the sea squirt cellulose nanocrystals are more likely to form cross-linking points in the early stage of the reaction, promote the rapid formation of hyperbranched cores, provide a stable structural basis for hyperbranched polymers, and have optical properties, which improves the transmittance of the resin; rice husk cellulose nanocrystals are smaller in size and are easier to distribute around the formed core, fill the gaps, and form a dense shell, which not only improves the density and hardness of the polymer, but also further improves its mechanical properties. At the same time, rice husk cellulose nanocrystals have good biocompatibility and degradability, which improves the biological safety of resin surface contact and reduces toxicity; due to their denser core-shell structure and enhanced intermolecular interaction, they can better resist the influence of environmental factors such as ultraviolet rays and oxidation, thereby extending their outdoor service life.
[0018] Third, the surface of the modified cellulose nanocrystals carries anions and cations, which form ionic bonds or electrostatic interactions with the corresponding ions or functional groups in the resin matrix, thereby significantly enhancing the binding force between the cellulose nanocrystals and the resin matrix, making the cellulose nanocrystals more stable in the resin, not easy to fall off or disperse, and improving the overall performance of the resin.
[0019] Fourth, the untreated nanofiber crystals have a higher degree of crystallinity, which improves the mechanical properties and thermal stability of the composite material; while the microwave-treated nanofiber crystals have lower crystallinity, better dispersibility, and improved processing performance; the mixed use of the two can improve the processing performance while maintaining certain mechanical properties and thermal stability; the mixed use of untreated and microwave-treated nanofiber crystals forms a more complex interface structure; the untreated nanofiber crystals form a more stable network structure, while the microwave-treated nanofiber crystals can better fill the network gaps, improve the interface bonding strength and the density of the composite material; the mixed use of untreated and microwave-treated nanofiber crystals produces a synergistic effect, that is, the interaction between the two makes the performance of the composite material better than when one of the nanofiber crystals is used alone. DETAILED DESCRIPTION
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items. Embodiment 1
[0021] The present application discloses a method for preparing a styrene-free unsaturated polyester resin, which specifically comprises: S1, cellulose nanocrystals, tris(2-hydroxyethyl)isocyanurate and dimethylolpropionic acid are mixed with nitrogen, and the temperature is slowly raised to 120°C and then stirred. The reaction temperature is 120-140°C, and the cellulose nanocrystals are added for the second time when the acid value of the reaction system is 100 mgKOH / g, and the stirring is continued until the acid value of the reaction system is ≤2 mgKOH / g to obtain a hydroxyl-containing hyperbranched polyester; the mass ratio of cellulose nanocrystals, tris(2-hydroxyethyl)isocyanurate and dimethylolpropionic acid is 1:3:6, wherein the cellulose nanocrystals added for the first time account for 30%-60% of the total amount; Cellulose nanocrystals are prepared by extraction from sea squirts; S2, lowering the temperature of the hydroxyl-containing hyperbranched polyester reaction system to 50° C., adding maleic anhydride, slowly heating to 120° C., reacting until the acid value is 260 mgKOH / g, to obtain a carboxyl-containing hyperbranched polyester; wherein the mass ratio of the hydroxyl-containing hyperbranched polyester to the maleic anhydride is 4:5; S3, lowering the temperature of the carboxyl-containing hyperbranched polyester reaction system to 50° C., adding ethylene glycol monoallyl ether, passing nitrogen, slowly heating to 180° C., reacting until the acid value is 18 mgKOH / g, terminating the reaction, and obtaining a hyperbranched unsaturated polyester; the mass ratio of the carboxyl-containing hyperbranched polyester to ethylene glycol monoallyl ether is 5:2; S4. Diluting the hyperbranched unsaturated polyester with hydroxyethyl methacrylate to obtain a styrene-free hyperbranched unsaturated resin; the mass ratio of hydroxyethyl methacrylate to the hyperbranched unsaturated polyester is 3:5.
[0022] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: By adding cellulose nanocrystals in batches, the rate at the initial stage of the reaction is slowed down, making the reaction more stable and controllable, reducing side reactions and uneven product distribution caused by too fast a reaction rate, and keeping the raw material concentration in the reaction system within a relatively stable range, which is conducive to the smooth progress of the reaction and allows the reaction to gradually deepen, thereby obtaining hyperbranched polyesters with narrower molecular weight distribution and more uniform structure, and improving key indicators such as mechanical properties and heat resistance of the resin; adding raw materials in batches changes the kinetics of the reaction, adjusts the reaction path and the stability of the intermediates, and adding some cellulose nanocrystals at the initial stage of the reaction promotes the initial formation of a hyperbranched structure; as the reaction proceeds, gradually adding the remaining raw materials can further improve and optimize the hyperbranched structure; The newly added cellulose nanocrystals participate in the hyperbranched polymerization reaction, which expands the molecular chain and increases the branching, thereby changing the molecular weight distribution and branching degree of the final polymer, and the newly added cellulose nanocrystals are more concentrated on the shell structure of the hyperbranched polymer, so that a certain number of cellulose nanocrystals are distributed on the core-shell structure of the hyperbranched polymer, and the flame retardant ability of the resin is improved, and the steric hindrance of the branch chain is increased, and the entanglement of the branch chain is further reduced, and the viscosity of the resin is reduced; and the already formed hyperbranched polymer undergoes structural reorganization due to the newly added cellulose nanocrystals, making the internal structure of the polymer more complex and diverse, and the cellulose nanocrystals contain a large number of hydroxyl groups, which form hydrogen bonds with the hydroxyl groups or other functional groups in the already formed hyperbranched polymer, thereby enhancing the interaction between polymer molecules and improving the cellulose nanocrystals. The dispersion of nanocrystals in the resin matrix prevents the agglomeration of cellulose nanocrystals, thereby reducing the hindrance to the fluidity of the resin and lowering the viscosity of the resin. The formation of hydrogen bonds enhances the interaction between polymer chain segments, making the movement between the chain segments no longer completely independent, and allowing the chain segments to move more cooperatively when subjected to external forces. Although hydrogen bonds enhance the interaction between the chain segments, this force is not rigid. On the contrary, hydrogen bonds have a certain flexibility and variability, allowing the chain segments to move flexibly within a certain range. In polymers, entangled structures often form between the chain segments, and the formation of hydrogen bonds helps to break these entangled structures, making it easier for the chain segments to disentangle and rearrange. The newly added cellulose nanocrystals are also regarded as fillers to a certain extent. They fill the voids in the hyperbranched polymers to improve the density and hardness of the polymer. Embodiment 2
[0023] The above embodiment not only improves the original low viscosity and flame retardancy by adding cellulose nanocrystals in batches, but also reduces side reactions, making the molecular weight distribution narrower and the structure more uniform. In order to improve the biocompatibility and stability of the resin, further improvements are made on the basis of embodiment 1.
[0024] The cellulose nanocrystals added for the first time are extracted from ascidian; the cellulose nanocrystals added for the second time are extracted from rice husks, wherein the rice husk cellulose nanocrystals have a length of 75-100nm and a diameter of 15-20nm, and the ascidian cellulose nanocrystals have a length of 500-2000nm and a diameter of 25-35nm.
[0025] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Due to their long length, sea squirt cellulose nanocrystals are more likely to form cross-linking points at the beginning of the reaction, promote the rapid formation of hyperbranched cores, provide a stable structural basis for hyperbranched polymers, and have optical properties, which improves the light transmittance of the resin; rice husk cellulose nanocrystals are smaller in size and are more likely to be distributed around the formed core, fill the gaps, and form a dense shell, which not only improves the density and hardness of the polymer, but also further improves its mechanical properties. At the same time, rice husk cellulose nanocrystals have good biocompatibility and degradability, which improves the biological safety of resin surface contact and reduces toxicity; due to their denser core-shell structure and enhanced intermolecular interaction, they can better resist the influence of environmental factors such as ultraviolet rays and oxidation, thereby extending their outdoor service life; The distribution of the two cellulose nanocrystals of different shapes in the resin complements each other. The sea squirt cellulose nanocrystals form the core, and the rice husk cellulose nanocrystals fill the shell layer, which reduces the agglomeration of the cellulose nanocrystals and improves their dispersibility in the resin matrix. At the same time, the hydroxyl groups on the cellulose nanocrystals form hydrogen bonds with the functional groups in the hyperbranched polymer, which enhances the interaction between molecules and makes the polymer structure more stable. Since the rice husk cellulose nanocrystals are filled in the shell layer, a protective layer is formed, which further improves the flame retardant properties of the resin. During the combustion process, the shell layer slows down the spread of the flame and prevents the transfer of heat and oxygen. Embodiment 3
[0026] Embodiment 2 The weather resistance and stability of the resin are increased by using two different cellulose nanocrystals in combination. In order to further improve its stability and increase its service life, further improvements are made on the basis of Embodiment 2.
[0027] The cellulose nanocrystals are also ion-modified before use, wherein the sea squirt cellulose nanocrystals are loaded with anions, and the rice husk cellulose nanocrystals are loaded with cations. Specifically, the sea squirt cellulose nanocrystals and citric acid are respectively dissolved in water, then mixed evenly, stirred overnight, and then dried and ground; the rice husk cellulose nanocrystals and DTAB are respectively dissolved in water, then mixed evenly, stirred overnight, and then centrifuged and filtered to dry; the citric acid aqueous solution is a saturated or supersaturated solution, the concentration of the DTAB aqueous solution is 10 mol / L, and the cellulose nanocrystals are a 5% solution by mass.
[0028] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The modified cellulose nanocrystals have anions and cations on their surfaces, which form ionic bonds or electrostatic interactions with the corresponding ions or functional groups in the resin matrix, thereby significantly enhancing the binding force between the cellulose nanocrystals and the resin matrix, making the cellulose nanocrystals more stable in the resin and less likely to fall off or disperse, thereby improving the overall performance of the resin. By adjusting the charge density and type of the surface of cellulose nanocrystals, the dispersion state of cellulose nanocrystals in the resin is controlled, the occurrence of agglomeration is effectively reduced, and the microstructure of the resin is made more uniform; loading ions with catalytic activity can make the resin catalytic and used to catalyze chemical reactions; loading ions with antibacterial properties can make the resin antibacterial and used to prepare antibacterial materials. The interaction between the modified cellulose nanocrystals and the resin matrix is tighter and more stable, which improves the overall stability of the resin; during long-term use, it can resist the erosion and damage of the external environment and maintain the durability and reliability of the resin performance. Due to the enhancement of the interface interaction, the modified resin has higher mechanical properties such as tensile strength, bending strength and impact toughness; the formation of ionic bonds and electrostatic interactions improves the thermal stability of the resin, enabling it to maintain stable performance at higher temperatures. The modified resin has stronger resistance to environmental factors such as ultraviolet rays and oxidation, which extends its service life in outdoor environments. By loading different types of ions, the resin is endowed with a variety of new functional properties to meet different application requirements; After the sea squirt cellulose nanocrystals are loaded with anions, their surface properties change, and the interfacial compatibility with the resin matrix or other materials is enhanced, which improves the mechanical properties of the composite material, and increases the tensile strength and bending modulus; the sea squirt cellulose nanocrystals loaded with anions have stronger flame retardant properties, and the anions interact with the resin matrix to form a more stable flame retardant system, thereby improving the flame retardant grade and flame retardant durability of the material; the anions improve the dispersibility of the sea squirt cellulose nanocrystals in the resin matrix, reduce the occurrence of agglomeration, and give the composite material new functional properties, such as antibacterial, antistatic, and conductive. After rice husk cellulose nanocrystals are loaded with cations, their surfaces carry more positive charges, thereby enhancing the adsorption performance for anionic pollutants or harmful substances, and can be better applied in environmental treatment, water treatment and other fields; rice husk cellulose nanocrystals loaded with cations show higher catalytic activity in certain catalytic reactions, and cations can serve as catalytic active centers to promote the reaction and improve catalytic efficiency. The presence of cations helps to improve the compatibility between rice husk cellulose nanocrystals and organisms and reduce the occurrence of rejection reactions; making rice husk cellulose nanocrystals loaded with cations have potential application value in the biomedical field, such as as drug carriers, biosensors, etc.; the loading of cations may enhance the stability of rice husk cellulose nanocrystals in harsh environments and improve their performance under acidic or alkaline conditions. The corrosion resistance of rice husk cellulose nanocrystals can be improved, which broadens the application scope of rice husk cellulose nanocrystals, especially in harsh environments; and the combined use of the two makes it possible for the cellulose nanocrystals in the core and shell to attract each other during the preparation and use process to prevent falling off, increase stability and durability, better resist physical damage and chemical corrosion, and attract each other to form a more stable network structure, thereby improving the bearing capacity and impact resistance of the resin, and enhancing the interfacial adhesion between the resin and the matrix material, thereby improving the overall performance of the composite material. The introduction of cellulose nanocrystals forms a large number of interfacial areas in the resin matrix. When the cellulose nanocrystals in the core and the cellulose nanocrystals in the shell attract each other, these interfacial areas become more stable, thereby enhancing the interaction between the resin and the cellulose nanocrystals. Embodiment 4
[0029] Example 3 increases the weather resistance stability and service life of the resin by ion loading. In order to improve the mechanical properties of the resin material and broaden the application field, further improvements are made on the basis of Example 3.
[0030] The rice husk cellulose nanocrystals are also subjected to microwave treatment before modification, specifically: 500 watts of power for 10 minutes, wherein the microwave-treated rice husk cellulose nanocrystals account for 20-80% of the total mass, and the concentration of the DTAB aqueous solution is 1-20 mol / L.
[0031] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: After reducing the crystallinity through microwave treatment, the particle size of the nanofiber crystals becomes more flexible, which is conducive to their uniform dispersion in the resin, thereby improving the overall performance of the composite material. The reduction in crystallinity also increases the active sites on the surface of the nanofiber crystals, forming a stronger interaction with the functional groups in the resin matrix, and improving the mechanical properties and heat resistance of the composite material. The addition of nanofiber crystals themselves will increase the viscosity of the resin to a certain extent, but the nanofiber crystals treated with microwaves slow down this increasing trend due to their better dispersibility and more flexible molecular chains, further reducing the viscosity. At the same time, the introduction of nanofiber crystals is also beneficial to the fluidity of the resin by forming a network structure. After reducing the crystallinity of the nanofiber crystals, their distribution in the resin is more uniform, forming a denser core-shell structure, thereby improving the density and hardness of the composite material. At the same time, the increase in the active sites of the nanofiber crystals also helps to improve the flame retardant properties and weather resistance of the composite material.
[0032] High-crystallinity nanofiber crystals that have not been microwaved usually have higher rigidity and strength, which improves the mechanical properties of composite materials, such as tensile strength and bending modulus. High-crystallinity nanofiber crystals are not prone to structural changes when heated, which improves the thermal stability of the composite material and enables it to maintain stable performance at higher temperatures. High-crystallinity nanofiber crystals can form a more stable structure in the resin matrix, reduce the dimensional change of the composite material, and improve its dimensional stability. High-crystallinity nanofiber crystals themselves have certain flame retardant properties, and their addition to the resin matrix helps to improve the flame retardant properties of the composite material. Untreated nanofiber crystals have a higher degree of crystallinity, which improves the mechanical properties and thermal stability of the composite material; while microwave-treated nanofiber crystals have a lower degree of crystallinity, better dispersibility, and improved processing performance; mixing the two can improve processing performance while maintaining certain mechanical properties and thermal stability; Mixing untreated and microwave-treated nanofiber crystals forms a more complex interface structure; untreated nanofiber crystals form a more stable network structure, while microwave-treated nanofiber crystals can better fill the network gaps, improving the bonding strength of the interface and the density of the composite material; mixing untreated and microwave-treated nanofiber crystals produces a synergistic effect, that is, the interaction between the two makes the performance of the composite material better than when either nanofiber crystal is used alone; The microwave-treated nanofiber crystals have a lower crystallinity and better dispersibility in the resin matrix, which helps to disperse the untreated nanofiber crystals in the resin and reduce agglomeration; the untreated nanofiber crystals have a higher crystallinity and more active sites on the surface, which can form a stronger interface bond with the resin matrix, thereby improving the mechanical properties and stability of the entire composite material; the untreated nanofiber crystals have high crystallinity and strong rigidity, thereby improving the strength and hardness of the composite material; while the microwave-treated nanofiber crystals have a lower crystallinity and increased flexibility, thereby improving the toughness and impact resistance of the composite material; the mixed use of the two can achieve a balance between rigidity and flexibility, thereby optimizing the mechanical properties of the composite material; the untreated nanofiber crystals have a high crystallinity and usually have better thermal stability; in the mixed system, the untreated nanofiber crystals act as an "anchor point" to improve the thermal stability of the entire composite material. Although the microwave-treated nanofiber crystals have a lower crystallinity, they have better dispersibility and form a more uniform network structure, thereby improving the thermal stability of the composite material; After cation modification, the surface of the nanofiber crystal will be positively charged. There will be electrostatic repulsion between the positively charged particles, which will help their dispersion. When the amount of loading is reduced, there will be a difference in surface charge density or charge distribution between the treated nanofiber crystal and the untreated nanofiber crystal after cation modification. Then there will be electrostatic attraction, especially in the area with lower charge density, resulting in mutual attraction. For example, the rice husk cellulose nanocrystals treated with microwaves account for 50% of the total mass, the concentration of the DTAB aqueous solution is 1 mol / L, and the medium proportion of microwave-treated CNC balances rigidity and flexibility; low concentration DTAB modification maintains a certain interface bonding force, excellent comprehensive performance, both certain rigidity and good toughness, good processing performance, easy molding, suitable for composite materials that require a comprehensive performance balance, such as home appliance housings and sporting goods; The rice husk cellulose nanocrystals treated with microwaves account for 20% of the total mass, and the concentration of the DTAB aqueous solution is 10 mol / L. The microwave-treated CNC provides a certain flexibility, but the DTAB concentration is high, which enhances the electrostatic repulsion, better dispersion, excellent dispersion, improved uniformity of the composite material, better toughness and impact resistance; It is suitable for composite materials that require good dispersion and higher toughness, such as electronic packaging materials and coatings; The rice husk cellulose nanocrystals treated with microwaves account for 80% of the total mass, and the concentration of the DTAB aqueous solution is 20 mol / L. The high proportion of microwave-treated CNC increases the flexibility of the composite material. With the increase of DTAB concentration, the dispersibility gradually increases. It has extremely high flexibility and impact resistance, and is suitable for the preparation of flexible composite materials, such as flexible electronic devices and rubber products.
[0033] The styrene-free unsaturated resins prepared in Examples 1 to 4 of the present invention were tested, and the specific test results are shown in Table 1:
[0034] 0.2% accelerator, 6% Co-Naph and 1.5% curing agent AKZOM-50 were added to the styrene-free hyperbranched unsaturated resin prepared in Examples 1 to 4 of the present invention, and the casting method was carried out according to GB / T8237, and its stability was tested. The specific test results are shown in Table 2:
[0035] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a styrene-free unsaturated polyester resin, characterized in that: Specifically: S1, cellulose nanocrystals, tris(2-hydroxyethyl)isocyanurate and dimethylolpropionic acid are mixed with nitrogen, and the temperature is slowly raised to 120°C and then stirred. The reaction temperature is 120-140°C, and the cellulose nanocrystals are added for the second time when the acid value of the reaction system is 100 mgKOH / g, and the stirring is continued until the acid value of the reaction system is ≤2 mgKOH / g to obtain a hydroxyl-containing hyperbranched polyester; the mass ratio of cellulose nanocrystals, tris(2-hydroxyethyl)isocyanurate and dimethylolpropionic acid is 1:3:6; S2, lowering the temperature of the hydroxyl-containing hyperbranched polyester reaction system to 50° C., adding maleic anhydride, slowly heating to 120° C., reacting until the acid value is 260 mgKOH / g, to obtain a carboxyl-containing hyperbranched polyester; wherein the mass ratio of the hydroxyl-containing hyperbranched polyester to the maleic anhydride is 4:5; S3, lowering the temperature of the carboxyl-containing hyperbranched polyester reaction system to 50° C., adding ethylene glycol monoallyl ether, passing nitrogen, slowly heating to 180° C., reacting until the acid value is 18 mgKOH / g, terminating the reaction, and obtaining a hyperbranched unsaturated polyester; the mass ratio of the carboxyl-containing hyperbranched polyester to ethylene glycol monoallyl ether is 5:2; S4. Diluting the hyperbranched unsaturated polyester with hydroxyethyl methacrylate to obtain a styrene-free hyperbranched unsaturated resin; the mass ratio of hydroxyethyl methacrylate to the hyperbranched unsaturated polyester is 3:
5.
2. The method for preparing a styrene-free unsaturated polyester resin according to claim 1, characterized in that: The cellulose nanocrystals added for the first time account for 30%-60% of the total amount; the added cellulose nanocrystals are extracted and prepared from ascidian.
3. The method for preparing a styrene-free unsaturated polyester resin according to claim 1, characterized in that: The cellulose nanocrystals added for the second time were extracted and prepared from ascidian.
4. The method for preparing a styrene-free unsaturated polyester resin according to claim 1, characterized in that: The cellulose nanocrystals added for the second time were extracted and prepared from rice husks.
5. The method for preparing a styrene-free unsaturated polyester resin according to claim 4, characterized in that: The cellulose nanocrystals were also ionically modified before use.
6. The method for preparing a styrene-free unsaturated polyester resin according to claim 5, characterized in that: The rice husk cellulose nanocrystals are loaded with cations, specifically, the rice husk cellulose nanocrystals and DTAB are respectively dissolved in water and then mixed evenly, stirred overnight, and then centrifuged and filtered to dry.
7. The method for preparing a styrene-free unsaturated polyester resin according to claim 5, characterized in that: Ascidian cellulose nanocrystals loaded with anions.
8. The method for preparing a styrene-free unsaturated polyester resin according to claim 6, characterized in that: The concentration of the DTAB aqueous solution is 1-20 mol / L.
9. The method for preparing a styrene-free unsaturated polyester resin according to claim 8, characterized in that: The rice husk cellulose nanocrystals are also partially subjected to microwave treatment before modification, specifically: 500 watts of power for 10 minutes, wherein the microwave-treated rice husk cellulose nanocrystals account for 20-80% of the total mass.
10. A styrene-free unsaturated polyester resin, characterized in that: The polyurethane foam is prepared by the preparation method of the styrene-free unsaturated polyester resin according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of flame-retardant styrene-free hyperbranched unsaturated resin
CN114316234A
Preparation method of bio-based unsaturated polyester / nanocellulose anti-ultraviolet composite material
CN115232457A
Preparation method and application of cationic cellulose nanofiber flocculant
CN118206668A
Fiber-reinforced resin composition comprising chemically modified cellulose nanofibers and thermoplastic resin
US20180037737A1